Brief communication: Weak correlation between building damage and loss of life from landslides - M. Van Wyk de Vries; M. Van Wyk de Vries; M. Van Wyk de Vries; A. Dunant; A. Dunant; A. L. Johnson; E. L. Harvey; S. Li; K. Arrell; J. Baniya; D. Basnet; G. K. Basyal; et al. (Natural Hazards and Earth System Sciences)
Mapping exposure to landslides is necessary to mitigate risk and increase resilience. Exposure maps can be constructed from building databases, akin to seismic risk assessments, but there has been little investigation of the predictive relationship between building damage from landslides and risk to human life. Our study investigates this relationship globally and in Nepal (47 213 and 5664 landslides, respectively). While a correlation exists for nationwide totals (R2 = 0.75), it is negligible for individual events (R2 = 0.025). It is important to not construct landslide exposure maps from building datasets alone, else building damage may be inadvertently prioritised over human lives in disaster planning.